Bildzensur. Löschung technischer Bilder - Müller-Helle, Katja (Bildwelten des Wissens, 2020)
Technical censorship of pictures is omnipresent and invisible at the same time. Content moderation on social media and automatic deletions by algorithms have given rise to a new union of human and non-human protagonists. While traditional institutions of censorship regulated the impact of dangerous pictures based on legal and religious norms, automated mechanisms controlled by international corporations do so today. In the public sphere of technical pictorial worlds, upload filters, content moderation, or deepfakes have replaced markers of the visibility of deletion such as censor bars or pixilation. In this experimental phase of the modern digital age, what pictures circulate in the flow of data is once again being negotiated anew in technical, social, legal, and picture-theory terms.